Evaluation of the Influence of Technology Adoption Model Factors on the Successful Implementation of Artificial Intelligence Applications in Online Learning - Akis, Dwi Ihza Sari; Andi Rhyta Samantha Valda; Rizky Aulia; Rosidah; Andi Dio Nurul Awalia (Jurnal MediaTIK, 2025)
This research evaluates the successful implementation of artificial intelligence (AI) applications in online learning using the Technology Adoption Model approach. The main issues raised were how AI applications can influence student engagement and motivation to learn, and how challenges such as network stability and trust in data security can be overcome. A quantitative research method with a cross-sectional design involved 93 college students aged 18-22 who had experience using AI applications. Data were collected through a Likert scale questionnaire, covering aspects of convenience, ease of use, impact, trust, technical support, motivation, challenges, and influence on learning outcomes. The results showed that the AI application had a positive impact in increasing students' learning engagement and motivation. Respondents generally feel comfortable using this application and rate the technology as easy to use. However, challenges such as adaptation constraints, network stability, and doubts about data security are still obstacles. In conclusion, although the implementation of AI applications in online learning has shown positive results, improvements are needed on technical and privacy aspects to maximize the acceptance and effectiveness of this technology. This research makes an important contribution to the development of better AI implementation strategies in online education.